Identification and Fine Mapping of Nuclear and Nucleolar Localization Signals within the Human Ribosomal Protein S17 - Kenney, Scott P. (PLoS One, 2015)
Human ribosomal protein S17 (RPS17) is mutated in Diamond-Blackfan Anemia (DBA), a bone marrow disorder that fails to produce sufficient red blood cells leading to anemia. Recently, an RPS17 protein sequence was also found to be naturally inserted in the genome of hepatitis E virus (HEV) from patients chronically-infected by HEV. The role of RPS17 in HEV replication and pathogenesis remains unknown due to the lack of knowledge about how RPS17 functions at a molecular level. Understanding the biological function of RPS17 is critical for elucidating its role in virus infection and DBA disease processes. In this study we probed the subcellular distribution of normal and mutant RPS17 proteins in a human liver cell line (Huh7). RPS17 was primarily detected within the nucleus, and more specifically within the nucleoli. Using a transient expression system in which RPS17 or truncations were expressed as fusions with enhanced yellow fluorescent protein (eYFP), we were able to identify and map, for the first time, two separate nuclear localization signals (NLSs), one to the first 13 amino acids of the amino-terminus of RPS17 and the other within amino acids 30-60. Additionally, we mapped amino acid sequences required for nucleolar accumulation of RPS17 to amino acids 60-70. Amino acids 60-70 possess a di-RG motif that may be necessary for nucleolar retention of RPS17. The results from this study enhance our knowledge of RSP17 and will facilitate future mechanistic studies about the roles of RSP17 in hepatitis E and DBA disease processes.